Wave hydrodynamics around a multifunctional artificial reef, at Leirosa - Mendonça, A. C. (2012)
Submitted by Branca Maria Hilário Branco Alvarez (bbranco@lnec.pt) on 2012-10-09T09:55:48Z No. of bitstreams: 1 Journal of Coastal Conservation Planning and Management_2012_Marco_Mendonca_et_al.pdf: 1407753 bytes, checksum: a47c884d0070f0cbc4ce8dd7cddea912 (MD5)